Transforming reading abilities: Unleashing the power of scaffolding in Quizizz - Agus Sholeh; Lailatul Qodriyah (Universitas Muhammadiyah Malang, 2024)
This study aims to investigate the effectiveness of implementing a scaffolding strategy within the Quizizz web platform to enhance reading skills among university students and to determine whether there is a significant difference between students taught with and without the scaffolding strategy, both using Quizizz. The research utilized a quasi-experimental design and was conducted at Universitas PGRI Kanjuruhan Malang, targeting second-semester reading classes. The sample consisted of 36 students, evenly divided into an experimental group and a control group, each comprising 18 students. Data were collected using pre-tests and post-tests and analyzed using an independent t-test. The findings reveal a significant improvement in the reading skills of the experimental group compared to the control group, as indicated by higher post-test mean scores (86.1 vs. 72.2). The hypothesis testing via the independent sample t-test yielded a significant value of 0.001, which is below the threshold of 0.05, confirming the statistical significance of the results. The study concludes that the scaffolding strategy is effective in enhancing students' reading skills, making it easier for them to read quickly and comprehend text. The researchers suggest that applying scaffolding strategies in educational tools like Quizizz can provide substantial benefits to learners.